Investasi dan Dorongan Pertumbuhan Ekonomi Bisnis Mikro Islam di Indonesia - Harun Santoso; Yudi Siyamto (ITB AAS INDONESIA Surakarta, 2016)
The study aims to determine micro businesses in promoting growth of Islam in Indonesia. This research manifold qualitative research-based literature. Results from the study showed that micro businesses Islam is able to achieve 40 percent annually, much higher than conventional economic growth, which reached 19 percent annually in promoting economic growth in Indonesia. Keywords: Investment, Islamic of Micro Business, Economic Growth